Effectiveness of App-Based Basketball Scorers for Basketball Games - Ade Ros Riza; Filli Azandi; Zulpikar Ilham; Ramlan Sahputera Sagala; Fajar Sidik Siregar (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to find out how effective the success of application-based basketball scorers is in recapturing all events, both personal foul violations, foul teams, score / points etc., according to the FIBA scorer fortofolio in the FIBA match rulebook. The research method used is an experimental method by looking at the differences in the results of the actual scorer records with the results of application-based scorer records. The sample in this study is a student of the Faculty of Sports, Medan State University who took a course in basketball game management. From the results of the research data obtained for personal foul data obtained the value of r Q1 (Quarter round)= 0.9656, Q2= 0.7281, Q3= 0.8668 and Q4= 0.8150, for the foul team data obtained the value of r Q1= 0.9656, Q2= 0.7281, Q3= 0.8668 and Q4= 0.8150, for the data of point 1 score obtained r value Q1= 0.9161, Q2= 0.8989, Q3= 0.9444 and Q4= 0.9048. For the time out data carried out by each team, the values of r Q1 = 1, Q2 = 1, Q3 = 1 and Q4 = 1 from the results of the reliability test, it can be concluded that the scorer application for basketball games can be used to replace the manual scorer that has been used and the level of efficiency is also very high judging from the reliability test category which ranges from strong to very strong.